2013
DOI: 10.1111/1346-8138.12080
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of unresectable dermatofibrosarcoma protuberans on finger with imatinib mesylate and Mohs microsurgery

Abstract: and B-cell lymphoma. The onset of PNP in a patient with hematological malignancy can resemble TEN, and the clinical picture is initially indistinguishable. 4 We should be cautious that some PNP cases may show TEN-like skin lesions rather than Stevens-Johnson syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…One patient with recurred DFSP was treated with imatinib mesylate as a neoadjuvant therapy before MMS, because of multiple recurrences and the location of the tumor, which was on the finger web. 11 Imatinib 400 mg twice a day for 3 months followed by reduced dose, 400 mg once a day for 2 months, was prescribed. MMS was performed after reduction of tumor size with Imatinib treatment.…”
Section: Resultsmentioning
confidence: 99%
“…One patient with recurred DFSP was treated with imatinib mesylate as a neoadjuvant therapy before MMS, because of multiple recurrences and the location of the tumor, which was on the finger web. 11 Imatinib 400 mg twice a day for 3 months followed by reduced dose, 400 mg once a day for 2 months, was prescribed. MMS was performed after reduction of tumor size with Imatinib treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The National Comprehensive Cancer Network guidelines currently recommend that imatinib be considered in cases of DFSP recurrence after resection or in cases deemed unresectable [20]. Imatinib has been reported to show efficacy against DFSP [3][4][5][21][22][23][24], and a recent analysis of 2 phase II trials also reported its promising clinical activity [5]. However, imatinib-resistant cases have also been reported, and progressive disease tends to be observed more in FS-DFSP cases than in classical DFSP ones.…”
Section: Discussionmentioning
confidence: 99%